Metamorphic Rock-Hosted Orogenic Gold Deposit Type as a Source of Langkowala Placer Gold, Bombana, Southeast Sulawesi - Idrus, Arifudin; Nur, I.; Warmada, I. W.; Fadlin, Fadlin (Geological Agency, 2011)
DOI:Â 10.17014/ijog.v6i1.114In 2008, placer gold was discovered in Langkowala area (Bombana Regency), Southeast Sulawesi, Indonesia, and more than 60,000 traditional gold miners in the early 2009 have been operating by digging vertical pits and panning active stream sediments. The grade of placer gold ranges from 50 to 140 g/t. Local geological framework indicates that the placer gold is not related to volcanic rock-related hydrothermal gold deposit, e.g. epithermal, skarn or porphyry. This paper describes a preliminary study on possible primary deposit type as a source of the Langkowala (Bombana) secondary placer gold. A field study indicates that the Langkowala (Bombana) placer/paleoplacer gold is possibly related to gold-bearing quartz veins/veinlets hosted by metamorphic rocks particularly mica schist and metasediments in the area. These quartz veins/veinlets are currently recognized in metamorphic rocks at Wumbubangka Mountains, a northern flank of Rumbia Mountain Range. Sheared, segmented quartz veins/veinlets are of 2 cm to 2 m in width and contain gold in a grade varying between 2 and 61 g/t. At least, there are two generations of the quartz veins. The first generation of quartz vein is parallel to foliation of mica schist and metasediments with general orientation of N 300oE/60o; the second quartz vein generation crosscut the first quartz vein and the foliation of the wallrock. The first quartz veins are mostly sheared/deformed, brecciated, and occasionally sigmoidal, whereas the second quartz veins are relatively massive. The similar quartz veins/veinlets types are also probably present in Mendoke Mountain Range, in the northern side of Langkowala area. This primary gold deposit is called as â€˜orogenic gold typeâ€™. The orogenic gold deposit could be a new target of gold exploration in Indonesia in the future.